Strategies for Triggering Transformative Climate Change Pathways: . Towards ‘Fit for Purpose’ Philanthropic and Donor Engagement - Cashore, Benjamin William (Meridien Institute, 2021)
Climate and Land Use 2030: Resources for Funders